Computational modelling studies on discharge products of advanced lithium-sulphur batteries - Masedi, Mallang Cliffton (My University, 2018)
Beyond conventional intercalation chemistry, reaction of lithium with sulphur and oxygen (so-called “Li-air” batteries) have the potential to provide 2 to 5 times the energy density of current Li-ion battery systems. However, both Li/S and Li/O2 systems suffer from cycling performance issues that impede their commercial applications: Li/O2 cycling is limited by electrolyte decomposition and large cell polarization; Li/S suffers from the low conductivity of S and the solubility of intermediary polysulfide species during cycling. It has been reported that Se and mixed SexSy represent an attractive new class of cathode materials with promising electrochemical performance in reactions with both Li and Na ions. Notably, unlike existing Li/S batteries that only operate at high temperature, these new Se and Li/SexSy electrodes are capable of room temperature cycling. Initially, stabilities of insoluble discharge products of oxygen and sulphur in the Li-S and Li-O2 batteries were investigated using density functional theory within the generalized gradient approximation, and these were deduced from their structural, electronic and mechanical properties. The structural properties are well reproduced and agree to within 3% with the available experimental data. Li2S, Li2O and Li2O2 and Li2S2 structures all have negative heats of formations indicating that they are stable, however, that of Li2S2 structure was relatively high compared to others. Calculated phonon dispersion and elastic properties revealed that Li2O, Li2S and Li2O2 structures are mechanically stable and great agreement with experimental work. The Li2S2 structure displayed soft modes associated mainly with sulphur atoms vibrations in the a-b plane, hence it is not mechanically stable in agreement with the negative C13. Stable Li2S2 polymorphs were extracted from soft modes of calculated phonon dispersions along the gamma direction in the Brillioun zone. Temperature is known to have a significant impact on the performance, safety, and cycle lifetime of lithium-ion batteries (LiB). In order to explore properties of discharge products associated with Li/S and Li/Se batteries at different temperatures, molecular dynamics and cluster expansion methods were employed. The former was achieved by firstly deriving empirical interatomic potentials of Li2S and Li2Se which were fitted to experimental and DFT calculated data. The potentials were validated against available experimental and calculated structure, elastic properties and phonon spectra. In addition, complex high temperature transformations and melting of Li2S and Li2Se were reproduced, as deduced from molecular dynamics simulations. Both Li2S and Li2Se were found to withstand high temperatures, up to 1250K each which is a desirable in future advanced battery technologies. Furthermore, cluster expansion and Monte-Carlo simulations were employed to determine phase changes and high temperature properties of mixed Li2S-Se. The former generated 42 new stable multi-component Li2S-Se structures and ranked metastable structures by enthalpy of formation. Monte Carlo simulations produced thermodynamic properties of Li2S-Se system for the entire range of Se concentrations obtained from cluster expansion and it demonstrated that Li2S-Se is a phase separating system at 0K but changes to mixed system at approximately 350K which was confirmed by constructed by phase diagram of Li2S-Se system. It was finally demonstrated that molecular dynamics and Monte Carlo simulations techniques yield consistent results on phase separation and high temperature behavior of Li2S-Se at 50% of sulphur and selenium.
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2018
Keywords: Computational modelling; Lithium-sulphur batteries; Electric lighting, Arc.; Electric discharge lighting